Interpreting Qur’anic Verses on Contract Through The Lens of Socio-Economic Exegetical Approach - Achmad Nur Alfianto; Roma Wijaya (Jurnal Ilmu Ekonomi dan Bisnis Islam, 2025)
This article seeks to develop Islamic economic studies through the perspective of Qur’anic economic interpretation by positioning interpretation as a primary methodological framework in the development of Islamic economics. Qur’anic interpretation is not treated merely as a textual approach to scriptural verses, but as an analytical instrument that connects divine messages with contemporary socio-economic realities. Despite the growing discourse on Islamic economics, existing studies largely treat Qur’anic interpretation as a normative reference rather than as a systematic methodological framework for socio-economic analysis. This study adopts the adabī al-ijtimāʿī wa al-iqtiṣādīyah approach, which emphasizes the social and economic relevance of the Qur’anic text, and applies a thematic (maudhuʿī) method involving the identification of contract-related verses, linguistic analysis, and examination of the chronology of revelation within the socio-economic context of the ummah. The findings indicate that the concept of contract plays a central role in maintaining the balance of social relations and economic transactions. Furthermore, the study demonstrates that contracts entail binding legal implications from both a Sharīʿah (normative–religious) and a positive (practical–institutional) perspective within the Islamic economic system. This study contributes conceptually by strengthening Qur’anic interpretation as a methodological foundation for Islamic economic analysis.